Our colors - Tagame, Gengorō 1964- (Pantheon Graphic Library, 2022)
"Set in contemporary suburban Japan, "Our Colors" is the story of Sora Itoda: a sixteen-year-old aspiring painter who experiences his world in synesthetic hues of blues and reds, governed by the emotional turbulence of being a teenager. He wants to live honestly as a young gay man in high school, but that is still not acceptable in Japanese society. His best friend and childhood confidante Nao, a young woman whom everyone thinks is (or should be) his girlfriend; and it would be the easiest thing to play along -- she knows he is gay but knows, too, how hard it is to live one's truth in his situation. Sora's world changes forever when he meets Mr. Amamiya, a middle-aged gentleman who is the owner and proprietor of a local coffee shop, and who is completely, unapologetically out as a gay man. A mentorship and friendship ensues, as Sora comes out to him and agrees to paint a mural in the shop, and Mr. Amamiya counsels him (platonically) about how to deal with who he is. But it won't be easy. Mr. Amamiya paid a high price for his freedom of identity, and when a figure from his past suddenly appears, it becomes a prime example of just how complicated life can be." --